1981
DOI: 10.1038/bjc.1981.25
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma and exposure to chemicals, especially organic solvents, chlorophenols and phenoxy acids: a case-control study

Abstract: A number of men with malignant lymphoma of the histiocytic type and previous exposure to phenoxy acids or chlorophenols were observed and reported in 1979. A matched case-control study has therefore been performed with cases of malignant lymphoma (Hodgkin's disease and non-Hodgkin lymphoma). This study included 169 cases and 338 controls. The results indicate that exposure to phenoxy acids, chlorophenols, and organic solvents may be a causative factor in malignant lymphoma. Combined exposure of these chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
149
8
3

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 392 publications
(177 citation statements)
references
References 27 publications
17
149
8
3
Order By: Relevance
“…In addition, in several studies since the 1980s, exposure to herbicides has been investigated as a risk factor for NHL in general (Hardell et al, 1981(Hardell et al, , 1994Hoar et al, 1986;Persson et al, 1989;Zahm et al, 1990). Our results show an increased risk for all herbicides including phenoxyacetic acids, with the highest OR for exposure to MCPA.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, in several studies since the 1980s, exposure to herbicides has been investigated as a risk factor for NHL in general (Hardell et al, 1981(Hardell et al, , 1994Hoar et al, 1986;Persson et al, 1989;Zahm et al, 1990). Our results show an increased risk for all herbicides including phenoxyacetic acids, with the highest OR for exposure to MCPA.…”
Section: Discussionsupporting
confidence: 54%
“…NHL has been associated with exposure to other organic solvents (Hardell et al, 1981(Hardell et al, , 1994Olsson and Brandt, 1981). As for HCL, in studies from France and the UK, exposure to organic solvents gave OR values between 1.2 (CI 0.8-1.7) (Clavel et al, 1995) and 1.45 ) (Staines and Cartwright, 1993), but in another small study from the UK, no increased OR was found (McKinney et al, 1988).…”
mentioning
confidence: 99%
“…We found a significant association between exposure to phenoxyacetic acids and chlorophenols and malignant lymphoma, both NHL and Hodgkin disease (Hardell et al 1981). The results for NHL were also published separately (Hardell et al 1994) and have been replicated by other research groups both in Sweden (Persson et al 1989) and in other countries ; for updated review, see Hardell et al 2003).…”
Section: Phenoxyacetic Acids and Chlorophenolssupporting
confidence: 70%
“…Most hazardous among these dioxins was 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), one of the most toxic chemicals in the world and now classified as a group I human carcinogen The use of Hormoslyr was prohibited in Sweden in 1977, and chlorophenols were prohibited in January 1978. In our first study (Hardell et al 1981(Hardell et al , 1994, the attributable fraction for Hormoslyr was 13% and that for chlorophenols was 26%. A substantially lower attributable fraction of 3.0% for phenoxyacetic acids was calculated in a study on men and women in central Sweden (Persson et al 1989), but a small number of subjects in the study had been exposed to chlorophenols.…”
Section: Phenoxyacetic Acids and Chlorophenolsmentioning
confidence: 99%
See 1 more Smart Citation